Pengaruh K3 (Keselamatan dan Kesehatan Kerja), Beban Kerja dan Kompensasi Terhadap Kepuasan Kerja Karyawan Shopee Ekspress Hub Medan Deli - Mutiara Andini; Shofyan Roni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Based on the partial test results, it is known that Occupational Health and Safety (K2) has a positive and significant effect on employee job satisfaction. The calculated t-value is 3.541 > t-table 2.009, therefore, the partial test conclusion is that H1 is accepted. The workload variable has a positive and significant effect on employee job satisfaction. The calculated t-value is 2.669 > t-table 2.009, therefore, the partial test conclusion is that H2 is accepted. The compensation variable has a positive and significant effect on employee job satisfaction. The calculated t-value is 2.053 > t-table 2.009, therefore, the partial test conclusion is that H3 is accepted. The simultaneous test results show that the variables K3 (X1), workload (X2), and compensation (X3) collectively have a positive and significant effect on employee job satisfaction at Shopee Ekspress Hub Medan Deli.